Harnack inequality under the change of metric - Tasena,S. (Elsevier Limited, 2015)
© 2014 Elsevier Ltd. All rights reserved. In this work, we give a sufficient and necessary condition in which the (parabolic) Harnack inequality of the original space would imply that of quasi-conformal spaces. The result can be applied to a large class of functions with discrete singularities.